Size structure, sex ratio, and breeding season in two intertidal grapsid crab species from Mar Chiquita Lagoon, Argentina - Spivak, Eduardo D; Anger, Klaus; Bas, Claudia C; Luppi, Tomás A; Ismael, Deborah (Revista Nerítica, 2022)
Life history patterns of two grapsid crab species were studied in Mar Chiquita, a brackish coastal lagoon in Argentina. Chasmagnathus granulata is a burrowing crab living in the upper intertidal, whereas Cyrtograpsus angulatus lives predominantly in the lower intertidal and subtidal. C. granulata is active (i.e. foraging and reproducing) during spring, summer and most of autumn, but remains mostly hidden inside its burrows during winter. Two dominant size groups each were found in the size-frequency distributions of males and females. Since this species builds elaborated and rather stable burrows, we found a rather uniform spatial distribution and a stable sex ratio, with only weak local deviations from a 1:1 ratio. In C. angulatus, which is a very mobile species, the sex ratio varied greatly in time and space, indicating local migrations with differential intensities or directions in males and females. Adult size structure in this species was similar at different sampling sites, with size frequency distribution of males revealing three dominant size groups, but that of females only one or two. In late autumn, most individuals of this species leave the intertidal zone and stay during winter in deeper water. Both species show a pronounced seasonal reproductive activity pattern, with a maximum percentage of ovigerous females found in the beginning of summer, and both appear to produce several subsequent egg clutches until late summer. The reproductive season is longer in C. angulatus (September-May; a few ovigerous females were found also in winter) than in C. granulata (October-March). In the intertidal, a low percentage of C. angulatus was observed to carry eggs in late embryonic stages. This suggests that ovigerous females of this species may migrate to the subtidal to release their larvae in deeper water.